Comparative analysis of clinicopathological characteristics in young and elderly patients with oral squamous cell carcinoma: a retrospective study in Northeastern Brazil - Pedro Augusto Bulhões CURIOSO; Ivan José CORREIA NETO; Lucas Lacerda de SOUZA; Edilmar de Moura SANTOS; Alan Roger SANTOS-SILVA; Pablo Agustin VARGAS; Marcio Ajudarte LOPES (Brazilian Oral Research)
Abstract The aim of this study was to perform a clinicopathological analysis of oral squamous cell carcinoma (OSCC) in young patients from the northeast of Brazil and compare with elderly individuals. This retrospective study reviewed 104 OSCC cases from 2000 to 2015, focusing on patients under 40 and over 60 at diagnosis. Forty-two patients under 40 years old (40.38%) and 62 patients over 60 years old (59.62%) were analyzed using descriptive statistics, chi-square, and Fisher’s exact tests for clinicopathological factors, and Kaplan-Meier and Cox models for survival and prognostics. Most of the patients were male, with younger patients having lower rates of smoking (45.24%) and alcohol use (28.57%) compared to older patients (82.30% and 40.32%, respectively). Younger patients had a higher prevalence of tongue cancer and smaller tumors but faced more compromised surgical margins, perineural invasion, local recurrence, regional metastasis, distant metastasis, and second primary tumors. Statistical findings highlighted age-related differences in clinicopathological features and indicated that despite similar overall survival rates, younger patients had a poorer prognosis related to local recurrences, regional recurrences, and second tumors. Perineural invasion emerged as an independent prognostic factor. The study suggests that younger OSCC patients require personalized management strategies to address their higher risk of adverse outcomes, with an emphasis on the prognostic significance of perineural invasion.